The Birth History of Sharia Financial Institutions and Their Contribution to the Economic Development of the Ummah in Indonesia - Zulkarnain; Arif, Zainal (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Research on the history of the birth of Sharia financial institutions and their contribution to development in Indonesia was carried out in November - December 2024. This research aims to analyze the history of the birth of Sharia financial institutions and their development since their inception, as well as their contribution to the economic development of the people in Indonesia. This research uses literature review and historical review methods from various sources from books and journals. The research results explain that Islamic financial institutions were born as an alternative solution to conventional system financial institutions, which were considered not by Islamic principles, especially in terms of riba (interest), gharar (uncertainty), and maysir (gambling) transactions. As time changes, Sharia financial institutions in Indonesia are proliferating, covering various types of institutions, ranging from Sharia banks, Sharia microfinance institutions, and Sharia insurance to Sharia capital markets. The presence of Sharia financial institutions has gained public trust and has been proven to contribute to the economic development of the people in Indonesia.